(3TQM GdETGQGJs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3jHOC bHd GdaUd GdQGHY Hbdjd GdaUd GdQGHY ai GfbSGe GdefWb Edi Gdbhd GdTGQM s
(3BNQgG (B:s
(3jfJgi HCKfGA GdaUd GdSGHY GdfUjMI Hbhdg (B: (3ajLH Ydi GdYbd GPG SeY TjFkG Gf dGjHGOQ Edi GacGQg Hd jQLY Edi GdMLI aEf bGeJ Ydjg s
(3HgG fXGe GdJYbjHIs
(3hQO GdYfhGf GdCUdi ai cTa GdXfhf L(B1 / 94s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdadSaI hGdefWbs